Abundant and metabolically flexible bacterial lineages underlie a vast potential for rubisco-mediated carbon fixation in the dark ocean - Alexander L. Jaffe; Rebecca S. R. Salcedo; Anne E. Dekas (Genome Biology, 2025)
Abstract Background Rubisco is among the most abundant enzymes on Earth and is a critical conduit for inorganic carbon into the biosphere. Despite this, the full extent of rubisco diversity and the biology of organisms that employ it for carbon fixation are still emerging, particularly in unlit ecosystems like the deep sea. Results We generate fifteen metagenomes along a spatially resolved transect off the California coast and combine them with globally distributed public data to examine the diversity, distribution, and metabolic features of rubisco-encoding organisms from the dark water column. Organisms with the form I and/or form II rubisco are detected in the vast majority of all samples and comprise up to around 20% of the binned microbial community. At 150 m and below, the potential for autotrophic carbon fixation via rubisco is dominated by just two orders of gammaproteobacteria and SAR324, encoding either the form I or II rubisco. Many of these organisms also possess genes for the oxidation of reduced sulfur compounds, which may energetically support carbon fixation. Transcriptomic profiling in the epi- and mesopelagic suggests that all major forms of rubisco (I, II, and III) can be highly expressed in the deep water column but are not done so constitutively, consistent with metabolic flexibility. Conclusions Our results demonstrate that the genetic potential to fix carbon via rubisco is significant and spatially widespread in the dark ocean. We identify several rubisco-encoding species that are particularly abundant and cosmopolitan, highlighting the key role they may play in deep-sea chemoautotrophy and the global marine carbon cycle.